7, 8-Dihydroxyflavone suppresses proliferation and induces apoptosis of human osteosarcoma cells. (21st May 2021) - Zhao, Jing; Li, Peifeng; Zhu, Hua; Ge, Fengqin; Liu, Jie; Xia, Jingjun; Hang, Pengzhou
Abstract: Recent studies suggest that 7, 8-dihydroxyflavone (7, 8-DHF) inhibits the development of several tumors. However, its role in osteosarcoma (OS) remains unknown. This study was designed to investigate the effects and underlying mechanisms of 7, 8-DHF that may influence OS development. Human OS cell lines (U2OS and 143B) were treated with 7, 8-DHF; cell viability and cell migration were assessed by methylthiazolyldiphenyl-tetrazolium bromide (MTT) assay and wound-healing assay, respectively; and cell death and apoptosis were evaluated by LIVE/DEAD staining and terminal deoxynucleotidyl transferase (TdT) dUTP nick-end labeling (TUNEL) assay, respectively. Reactive oxygen species production was measured using 2, 7-dichlorodihydrofluorescein diacetate probe. Akt, Bcl-xL/Bcl-2 asociated death promoter (Bad), p38 mitogen-activated protein kinase (MAPK), extracellular regulated protein kinase (ERK), and c-Jun N-terminal kinase (JNK) expression and their respective phosphorylation levels were detected by western blot analysis. We found that 7, 8-DHF reduced cell viability in a dose-dependent manner and also promoted apoptosis, inhibited migration, and induced oxidative stress in OS cells. Moreover, 7, 8-DHF inhibited Akt, Bad, and p38MAPK, but activated ERK and JNK signals. In summary, our results suggest that 7, 8-DHF inhibits OS progression, possibly by regulating Akt/Bad and MAPK signaling. These findings provide new evidence for the pharmacological effects of 7, 8-DHF that may improve drug therapy for OS patients.